Forage potential of experimental soybean lines (Glycine max) - Garay-Martínez , Jonathan Raúl; Maldonado-Moreno, Nicolás; Ascencio-Luciano, Guillermo; Joaquín-Cancino, Santiago; Bautista-Martínez , Yuridia; Granados-Rivera, Lorenzo Danilo (Ecosistemas y Recursos Agropecuarios, 2021)
Five experimental lines (H15-0625, H15-0249, H14-0307, ​​H14-0496 and H10-0556) and two commercial varieties (Huasteca 200 and Huasteca 300) of soybean [Glycine max (L.) Merr.] Were evaluated at 77, 91 and 105 days after sowing (DAS). The variables were crop growth rate (CGR), total dry matter (TDM), crude protein (CP), total digestible nutrients (TDN) and metabolizable energy (ME). A completely randomized design with four repetitions (Tukey; ɑ=0.05) was used. Lines H10-0556 and H14-0496, presented the highest (p<0.05) CRG, which on average were 100, 132 and 123 kg ha-1 d-1; while H10-0556 and H14-0496 presented higher (p<0.05) TDM yield, 7.689, 11.981 and 12.921 t ha-1, at 77, 91 and 105 DAS, respectively. No changes (p>0.05) were observed in the CP content between the different samplings, which on average was 171 g kg-1. The materials H14-0496, H15-0625 and Huasteca 300 presented higher (p<0.05) TDN, on average 580, 654 and 708 g kg-1 at 77, 91 and 105 DAS, respectively. The highest ME was presented by H14-0496, H15-0625 and Huasteca 300, 2.57 Mcal kg-1 on average, at 105 DAS. Of the materials evaluated, the experimental lines H10-0556, H14-0307 and H14-0496, presented the best forage potential than the commercial varieties, due to the higher forage yield and nutritional value. These lines could be harvested between 91 and 105 DDS, since they maintain the nutritional value of the forage.